The Vanguard of the Atlantic World : Creating Modernity, Nation, and Democracy in Nineteenth-Century Latin America - Sanders, James E., 1971- (Book collections on Project MUSE., 2014)
In the nineteenth century, Latin America was home to the majority of the world''s democratic republics. Many historians have dismissed these political experiments as corrupt pantomimes of governments of Western Europe and the United States. Challenging that perspective, James E. Sanders contends that Latin America in this period was a site of genuine political innovation and popular debate reflecting Latin Americans'' visions of modernity.